2022
DOI: 10.1177/00219983221084770
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of ultrasonically assisted exfoliated MWCNTs by ZrO2 nanoparticles on thermo-mechanical and anti-corrosive properties of epoxy nanocomposites

Abstract: Exploiting the boundless potential of multi-walled carbon nanotubes (MWCNTs) is the critical issue in developing multifunctional nanocomposites. In this study, the MWCNTs are exfoliated by ZrO2 nanoparticles using the ultrasonication technique. The obtained MWCNT/ZrO2 hybrid nanofiller is infused in the epoxy matrix to produce multifunctional nanocomposites with superior thermo-mechanical and anti-corrosive properties. The physical, morphological, and structural properties of MWCNT/ZrO2 hybrid nanofiller are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Tremendous efforts have been devoted to dispersing CNTs in the solvent and polymer matrix uniformly. Various methods, such as the addition of surfactants, mechanical stirring and grinding, ultrasonic dual mixing technique, and functional group modification, have been widely applied to CNTs to improve their dispersibility [ 50 , 51 , 52 , 53 , 54 , 55 , 56 ], thereby enabling the resultant nanocomposites to possess prominent mechanical, viscoelastic, and conductive properties.…”
Section: Dispersion Strategies Of Cntsmentioning
confidence: 99%
“…Tremendous efforts have been devoted to dispersing CNTs in the solvent and polymer matrix uniformly. Various methods, such as the addition of surfactants, mechanical stirring and grinding, ultrasonic dual mixing technique, and functional group modification, have been widely applied to CNTs to improve their dispersibility [ 50 , 51 , 52 , 53 , 54 , 55 , 56 ], thereby enabling the resultant nanocomposites to possess prominent mechanical, viscoelastic, and conductive properties.…”
Section: Dispersion Strategies Of Cntsmentioning
confidence: 99%
“…[6][7][8][9][10] Among them, the carbon nanotube (CNT)-reinforced polymer nanocomposite is one of the most popular materials indicating excellent mechanical, thermal and electrical properties at a low level of CNTs. [11][12][13][14][15][16] For example, Rathi and Kundalwal 13 observed that the addition of the hybrid structure of CNT/ZrO 2 (1.0 wt.%) in epoxy matrix can provide 67.8% and 58.04% enhancement in the tensile and lap shear strength of resulting nanocomposites. Theoretical and experimental evaluations have revealed that CNTs can possess a high tensile modulus of ∼1 TPa and high tensile strength of ∼11-63 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…Figure13. the uni-axial longitudinal loading, uni-axial transverse loading, bi-axial longitudinaltransverse loading and tri-axial longitudinal-transverse-transverse loading, interphase thickness is 10 nm and S max =100 MPa.…”
mentioning
confidence: 97%
“…One of the most commonly used matrices is epoxy (EP) resin, which is a highperformance structural polymer with exceptional mechanical properties, low shrinkage, good chemical and environmental resistances, and high dimensional stability. 25,26 However, the cross-linked structure and brittle nature of the virgin EP result in composites that have limited energy-absorption capacity or toughness. 27,28 Thus, in 3D fabric composites, matrix failure, fiber failure, and poor fiber-matrix interfacial interaction are important issues that need to be addressed to obtain high-performance structural composites.…”
Section: Introductionmentioning
confidence: 99%
“…While the mechanical performance of the composites largely depends on the reinforcement, the importance of the matrix cannot be overlooked. One of the most commonly used matrices is epoxy (EP) resin, which is a high‐performance structural polymer with exceptional mechanical properties, low shrinkage, good chemical and environmental resistances, and high dimensional stability 25,26 . However, the cross‐linked structure and brittle nature of the virgin EP result in composites that have limited energy‐absorption capacity or toughness 27,28 .…”
Section: Introductionmentioning
confidence: 99%